Carbon Quantum Dots sensitized Vertical WO3 Nanoplates with Enhanced Photoelectrochemical Properties. Issue 11 (22nd July 2016) - Zhao , Zhefei; Butburee, Teera; Peerakiatkhajohn, Piangjai; Lyu, Miaoqiang; Wang, Songcan; Wang, Lianzhou; Zheng, Huajun
Abstract: WO3 nanoplates (WO3 NP) sensitizing with carbon quantum dots (CQDs) photoanode was successfully fabricated by simple hydrothermal and immersing process under mild temperature. The as‐prepared composites were characterized by X‐ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), high‐resolution TEM, Raman spectrometer and ultraviolet visible spectrometry (UV‐vis). The WO3 photoanode after CQDs loading exhibited an enhanced photocurrent density of ∼1.18 mA cm −2 at 1.23 V vs RHE, compared to 0.96 mA cm −2 of pristine WO3 under simulated solar light illumination. Moreover, the modified WO3 nanoplates with CQDs show a superior ability to capture visible light, resulting in more than 1.6 folds of photocurrent density enhancement. Meanwhile, a lower onset potential can be obtained after sensitizing, which is caused by the change of band energy positions. Notably, this efficient sensitization of CQDs could introduce a promising route to improve the light harvesting and efficiency of photoelectrochemical properties for WO3 based photoanode. Abstract : This efficient sensitization of CQDs could introduce a promising route to improve the light harvesting and efficiency of photoelectrochemical properties for WO3 based photoanode. The CQDs and WO3 NP absorb light at different range and excite photogenerated electrons and holes, then the electrons on the CQDs will quickly transfer to the conduction band of the WO3 NP due to a local electric field so that the separation of photogenerated electron‐hole pairs could be promoted.